The association of sarcopenia and frailty in diabetes‐related foot disease: A 3‐year prospective evaluation - Kay Yee Hon; Madeleine Bain; Suzanne Edwards; Guilherme Pena; Neil McMillan; Robert Fitridge (Journal of Foot and Ankle Research)
Abstract Aim To prospectively evaluate the association of various markers of sarcopenia and frailty with clinical outcomes in diabetes‐related foot disease (DRFD), namely wound healing, amputation‐free survival, and death over 3 years. Methods This was an observational study of patients with DRFD at a quaternary multidisciplinary diabetic foot service. Initial assessment includes classification of DRFDs using WIfI classification, assessment of frailty using the FRAIL scale, and measurement of handgrip strength (HGS) using a dynamometer. Muscle mass was ascertained by measuring the psoas muscle area at the level of L3 vertebrae on computed tomography. Patients were followed up for 3 years and primary outcomes were wound healing, amputation‐free survival, and death. Results One hundred patients with a median age of 71 were included in the analysis. The majority of the patients were male (75%). Forty‐seven percent of patients were considered as frail, with 37 patients recorded to have low HGS. Patients with high HGS had significantly higher odds of wound healing by 3.83 times when compared to those with low HGS (odds ratio = 3.83. 95% CI 1.35–10.92). Patients with low psoas muscle index (PMI) and low HGS were observed to have a higher risk of death based on the following hazard ratios: HGS (high vs. low), HR = 0.46, 95% CI: 0.22–0.997; PMI (low vs. high), HR = 2.15, 95% CI: 1.17–3.96. Conclusion There was a significant prevalence of frailty and reduced HGS among our patients with DRFD. Low HGS was associated with poor wound healing and increased mortality in patients with DRFD. Additionally, low muscle mass was associated with increased mortality in this population. This research highlights the need for more precise tests and future studies of the links between sarcopenia, frailty, and outcomes in DRFD.